School functional assessment: performance in functional communication among special education at school / Nursyahirah Anuar, Rosilah Wahab - Anuar, Nursyahirah; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Functional communication is a critical skill used in school and students with special needs often have difficulties performing compared to their peers. The School Function Assessment (SFA) is able to contextually measure the performance of functional skill in special needs students and compare them between their peers within the Special Education Integration Program (SEIP) classes using the normreferenced criterion scores. 63 special needs students of eight different disabilities between ages seven to nine years old were assessed by their teachers in this research using the SFA (Part III) to investigate the relationship between age, gender and diagnosis with overall activity performance and performance in functional communication. The findings discovered that special needs students perform generally poorly across all components of SFA (Part III) and specifically in functional communication. There are no significant differences between gender (p=1.000) and ages (p = 0.095) with functional communication. There is also no significant differences were found between activity performance in functional communication and diagnosis (p=0.075). This research will increase understanding about the functional skill skills of special needs students of different age, gender and diagnosis and enable educators and therapists alike to plan effective interventions for the students.